Primary care clinicians' use of deprescribing recommendations: A mixed-methods study. Issue 8 (August 2022) - Mecca, Marcia C.; Zenoni, Maria; Fried, Terri R.
Abstract: Objective: to explore the effects of a deprescribing intervention on primary care clinicians' medication-related communication. Methods: A clinical decision support tool provided clinicians in the intervention group with an individualized report regarding potentially inappropriate medications (PIMs), deintensification of diabetes and/or hypertension treatment, and poor adherence/cognition. Participants included 113 Veterans aged ≥ 65 prescribed ≥ 7 medications and their primary care clinicians. Encounters were recorded and analyzed. Results: Between 36% and 38% of intervention clinicians discussed PIMs and diabetes mellitus/hypertension deintensification and 94% discussed adherence. PIMs discussions referred to the report and prompted some medication changes. The diabetes mellitus/hypertension and adherence discussions were not prompted by the report but instead arose from enhanced medication reconciliation. Changes in diabetes mellitus/hypertension medications were not made out of overtreatment concerns. There was no deprescribing for nonadherence. Enhanced medication reconciliation also led to discussions about medications not in the report. Conclusion: An individualized report regarding medication appropriateness prompted clinicians to perform a more thorough medication reconciliation and discuss PIMs. It did not prompt chronic care deintensification or deprescribing to enhance adherence. Practice Implications: Feedback reports can promote robust medication reconciliation in primary care. Changing clinician practice to achieve deprescribing in chronic disease management will be more challenging. Highlights: A medication feedback report impacts patient-provider communication in primary care. Providers who received reports conducted more robust medication reconciliation. Providers who received reports discussed potentially inappropriate medications. The report did not prompt clinicians to deintensify treatment of chronic diseases.